ha-Ish Moshe : studies in scriptural interpretation in the Dead Sea Scrolls and related literature in honor of Moshe J. Bernstein - Goldstein, Binyamin Y.; Segal, Michael, 1972.; Brooke, George J.; Bernstein, Moshe J. (Studies on the Texts of the Desert of Judah, 2017)
The eighteen studies in this volume in honor of Moshe Bernstein on the occasion of his 70th birthday mostly engage with Jewish scriptural interpretation, the principal theme of Bernstein's own research career as expressed in his collected essays, Reading and Re-Reading Scripture at Qumran (Brill, 2013). The essays develop a variety of aspects of scriptural interpretation. Although many of them are chiefly concerned with the Dead Sea Scrolls, the significant contribution of the volume as a whole is the way that even those studies are associated with others that consider the broader context of Jewish scriptural interpretation in late antiquity. As a result, a wider frame of reference for scriptural interpretation impinges upon how scripture was read and re-read in the scrolls from Qumran.